Advances in Non-Thermal Processing of Meat and Monitoring Meat Protein Gels Through Vibrational Spectroscopy - Huanhuan Li; Chenhui Li; Muhammad Shoaib; Wei Zhang; Arul Murugesan (Foods)
Meat is a vital source of high-quality proteins, amino acids, vitamins, and minerals essential for human health. Growing demand for healthier lifestyles and technological advancements has heightened the focus on meat products, whose quality depends on meat protein properties, such as texture, water holding capacity (WHC), and structural integrity. Non-thermal processing technologies are gaining attention for enhancing the gelation properties of meat protein gels (MPGs) by optimizing solubilization, denaturation, and aggregation while preserving nutritional and sensory qualities and avoiding the drawbacks of thermal treatments. This review focuses on advanced non-thermal processing techniques, including high-pressure processing (HPP), pulsed electric fields (PEFs), ultrasound, and cold plasma, and their impact on MPGs. It also examines vibrational spectroscopy methods, such as Fourier Transform Infrared (FTIR) and Raman spectroscopy, for non-invasive analysis of MPGs. The integration of these approaches with hyperspectral imaging and machine learning is also explored as a tool to improve quality control and assessment.